2019
DOI: 10.1002/nbm.4176
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the feasibility of creatine‐weighted CEST MRI in human brain at 7 T using a Z‐spectral fitting approach

Abstract: The current study aims to evaluate the feasibility of creatine (Cr) chemical exchange saturation transfer (CEST)‐weighted MRI at 7 T in the human brain by optimizing the saturation pulse parameters and computing contrast using a Z‐spectral fitting approach. The Cr‐weighted (Cr‐w) CEST contrast was computed from phantoms data. Simulations were carried out to obtain the optimum saturation parameters for Cr‐w CEST with lower contribution from other brain metabolites. CEST‐w images were acquired from the brains of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 52 publications
2
37
0
Order By: Relevance
“…Modified Bloch‐McConnell equations‐based simulations were used to generate CEST data for different pools (glutamate, amide and creatine) with different saturation parameters (Table 1). The saturation parameters for Glu‐w, 33 APT‐w 34 and Cr‐w 4 CEST were considered as used in reported studies. For all the metabolites, the simulations were carried out over a limited offset‐frequency range (Table 1) at a step size of 0.05 ppm, assumed to be ideal, or reference CEST data without any B 0 field inhomogeneity effects.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Modified Bloch‐McConnell equations‐based simulations were used to generate CEST data for different pools (glutamate, amide and creatine) with different saturation parameters (Table 1). The saturation parameters for Glu‐w, 33 APT‐w 34 and Cr‐w 4 CEST were considered as used in reported studies. For all the metabolites, the simulations were carried out over a limited offset‐frequency range (Table 1) at a step size of 0.05 ppm, assumed to be ideal, or reference CEST data without any B 0 field inhomogeneity effects.…”
Section: Methodsmentioning
confidence: 99%
“…The CEST MRI imaging parameters were slice thickness = 5 mm, GRE flip angle (FA) = 6 o , GRE readout TR/TE = 6/1. 4 The pulse sequence used in the current study for the acquisition of 2D APT-w MRI data has been reported previously. 2,8,34 The pulse comprised three sections: four blocks of RF saturation preparation pulses (each block with B 1rms = 2 μT, duration = 200 ms), each followed by a crusher gradient (duration = 10 ms, amplitude = 10 mT/m); lipid suppression (FA = 100 , duration = 17.…”
Section: Simulation Studymentioning
confidence: 99%
See 3 more Smart Citations